Avaliação dos parâmetros clínico-laboratoriais, histológicos e imuno-histoquímicos da cirrose criptogênica em pacientes submetidos ao transplante de fígado - Hanemann, Ana Lúcia de Paula (2019)
Liver cirrhosis is a clinical condition that represents the cast stage common to many chronic liver diseases. In some cases, even after detailed clinical, serological and pathological study, it is not possible to clarify the underlying chronic liver disease, in these cases cirrhosis. It is said to be cryptogenic or idiopathic. The aim of this study was to evaluate the clinical, laboratory, histological and immunohistochemical parameters of cryptogenic cirrhosis in patients undergoing liver transplantation. The research was developed at Walter Cantídio University Hospital. Fifty patients were selected from the following groups: liver donors (G-I), cirrhosis due to alcoholic steatohepatitis (G-II); hepatitis B cirrhosis (G-III), nonalcoholic steatohepatitis cirrhosis (G-IV) and cryptogenic cirrhosis (G-V). Clinical-laboratory and histopathological data were obtained retrospectively through revisions of reports, medical records and histopathological slides. For histopathological and immunohistochemical analysis, tissue microarray was made with biopsy samples for donor patients and explant samples for cirrhotic patients. Histological analyzes were evaluated using Ishak, Brunt and NAS (Nash activity score) scores. The following antibodies were selected for immunohistochemical analysis: PPARγ, PPARβ / δ, HBV-core, NF-κB and IL-6. In this study, it was observed that the majority of individuals with cryptogenic cirrhosis wasn’t is 50 years old (±17.67) with female predominance (70%) and a higher severity in Child-Pugh score (p=0.030). In the Ishak and Brunt scores, all groups presented cirrhosis degree with mild portal and septal inflammation (p<0.001). Comparing PPARγ immunoexpression in hepatocyte cytoplasm, between groups, it was found that group G-V had a higher frequency (p=0.009). For the PPARβ/δ antibody, groups G-II, G-III and G-IV (p<0.001) presented higher frequency of cytoplasmic labeling in hepatocytes. NF-κB was expressed in hepatocyte cytoplasm, especially in group G-II (p=0.026). Regarding IL-6 evaluated in kupffer cells, a higher immunoexpression was observed in groups G-II and G-IV (p=0.005). In the periportal / sinusoid region, IL-6 presented a higher frequency in groups G-II, G-III and G-IV (p=0.013). In the present research, it was observed that the histopathological predictors are not able to assist in the classification of the underlying cirrhosis disease in the advanced phase of the disease. In the evaluation of the possible etiological relationship between cryptogenic cirrhosis and steatohepatitis and hepatitis B, it was recognized that there was no causal relationship. As for immunohistochemical markers, PPARγ has been shown to be a critical transcription factor for reducing IL-6 expression and may cause a reduction in inflammatory infiltrate in the advanced phase of cryptogenic cirrhosis. Activation of PPARs ligands indicate a possible target of the regulatory functions of physiological mechanisms linked to energetic and inflammatory metabolism that could assist in the detection of major visualized changes in cryptogenic liver diseases. Key-words: Transplant. Cryptogenic cirrhosis. Immunohistochemical expression. Peroxisome proliferator activated receptor expression PPARβ / δ. PPARγ. IL-6. NF-κB.